Muslimah Participative Dakwah in Handling Domestic Violence in The Covid-19 Period - Pambayun, Ellys Lestari; Kadri, Wahab Nur; Saragih, Nurhayani; Ningrum, Desy Ayu (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study investigates the participation in da'wah by female preachers of 'Aisyiah in Bogor Regency to address the significant increase in domestic violence during the Covid-19 period. The lack of comprehension in the application of intersexual communication to solving economic, health, and educational problems for children is the primary factor in the emergence of both verbal and physical violence. Participatory methods to observe and encourage action and collaboration between female preachers of Aisyiah in Bogor Regency and volunteers, as well as in-depth observations and interviews, comprise the study's approach to da'wah and gender communication. Field analysis of data processing analysis. This study demonstrates that husbands committed more domestic violence against their women during the Covid-19 period as a result of deteriorating gender communication patterns due to emotional dominance and a lack of comprehension of Islamic values between partners. Therefore, it is necessary to approach gender communication based on the Qur'an and hadith in order to assist married couples in achieving inner balance.